Gradients of cyclic indentation mechanical properties in PR520 epoxy and its 3D carbon fiber composite induced by aging at 150 °C. (November 2021) - Pecora, M.; Smerdova, O.; Gigliotti, M.
Highlights: Cyclic indentation tests allowed to evaluate the effects of thermal aging on local elastic, plastic and viscoelastic properties of PR520 epoxy resin and its composite. Thermal aging affects the local plastic and elastic behavior, while viscoelastic response does not change between virgin and aged samples. Property gradient profiles measured through the thickness of resin and composite samples aged in the same conditions are well superposed. Abstract: A cyclic indentation test was carried out on PR520 epoxy resin and its 3D interlock carbon fiber reinforced composite in order to study the effects of thermo-oxidative aging on the material local properties. Thermal aging has been performed in air at 150 °C, which is close to the service temperature in warm zones of aircrafts, for different durations. Two parameters have been considered in this study: the reload indentation modulus, representative of the elastic response, and the ratio between irreversible and total indentation energy, representative of plastic (first cycle) and viscoelastic response. The analysis of cyclic indentation curves shows that elastic and plastic behavior are affected by thermal aging, while viscoelastic behavior is not. Moreover, a gradient of local properties has been measured through the thickness of aged samples. The affected zone extends of about 150 µm from the surface exposed to the oxidative environment, while the properties of the sample core are similar to those of the virgin material. Property gradient profiles measured on resin and composite aged in the same conditions are well superposed. Graphical abstract: Image, graphical abstract